2013
DOI: 10.1371/journal.pone.0060820
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Bioluminescent Imaging of Pre-Erythrocytic Malaria Parasite Infection Using Luciferase-Expressing Plasmodium yoelii

Abstract: The liver stages of Plasmodium parasites are important targets for the development of anti-malarial vaccine candidates and chemoprophylaxis approaches that aim to prevent clinical infection. Analyzing the impact of interventions on liver stages in the murine malaria model system Plasmodium yoelii has been cumbersome and requires terminal procedures. In vivo imaging of bioluminescent parasites has previously been shown to be an effective and non-invasive alternative to monitoring liver stage burden in the Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 20 publications
1
62
0
Order By: Relevance
“…1). These cells were cocultured with primary hepatocytes infected with luciferase-expressing P. yoelii spz (24), and parasite development was quantified as previously described (29). We observed that addition of 5 3 10 5 liver CD8 + T cells from CQ-or AS-ITVtreated mice significantly inhibited parasite development (81.2 and 78.5%, respectively) as compared with those from mockimmunized, untreated mice (Fig.…”
Section: Itv-induced Cd8 + T Cell Responses Are Cytotoxic To Ls Parasmentioning
confidence: 72%
See 1 more Smart Citation
“…1). These cells were cocultured with primary hepatocytes infected with luciferase-expressing P. yoelii spz (24), and parasite development was quantified as previously described (29). We observed that addition of 5 3 10 5 liver CD8 + T cells from CQ-or AS-ITVtreated mice significantly inhibited parasite development (81.2 and 78.5%, respectively) as compared with those from mockimmunized, untreated mice (Fig.…”
Section: Itv-induced Cd8 + T Cell Responses Are Cytotoxic To Ls Parasmentioning
confidence: 72%
“…using an RNeasy kit (Qiagen) following the manufacturer's instructions. cDNA generation and quantitative PCR (qPCR) were performed as previously described (24). The P. yoelii 18S rRNA signal was normalized to that of mouse GAPDH.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…Luciferase activity was measured 42 to 44 h after mosquito bite or i.v. challenge of mice with PyGFP-luc as previously described (34).…”
Section: Methodsmentioning
confidence: 99%
“…These approaches are mutually exclusive in the same animal, though, as qPCR analysis requires animal euthanasia and liver extraction prior to blood-stage infection -resulting in a doubling of animal numbers if both liver burden and time to patency are to be measured. Recently, measurement of liver-stage burden without animal sacrifice has become possible through live bioluminescent imaging techniques and the generation of parasites expressing the firefly luciferase gene [34,[66][67][68][69][70]. This approach strikes a balance between sensitivity of measuring liver-stage burden while keeping the animal alive to measure parasite progression to bloodstage patency, thus reducing animal use and also enabling recurrent challenge for investigation of duration of protection and immunological memory.…”
Section: Current Strategies To Identify and Validate Novel Pe Vaccine Tmentioning
confidence: 99%